THE RELATIONSHIP OF THE NUTRITIONAL STATUS OF PREGNANT WOMEN AND STUNTING IN TODDLER AT THE HUSADA CLINIC, JOMBANG - Kristian, Ike; Semi; Masyayih, Warda Anil (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2023)
Background: The occurrence of failure to thrive in children under five is caused by chronic malnutrition so that children under five are short according to their age, which is usually called stunting. One of the factors causing stunting is pregnancy. Pregnant women with CED (Chronic Energy Deficiency) cause the reserves of nutrients needed by the fetus in the womb to be weak. Objective: This study aimed to determine the relationship between the nutritional status of pregnant women and stunting in toddlers at the Husada Clinic, Jombang. Method: This research was conducted in July at the Husada Clinic, Jombang. This type of research is retrospective analytical. The population in this study was 55 toddlers with a sample of 33 toddlers. The sampling technique is simple random sampling. The independent variable in this research is the Nutritional Status of Pregnant Women, the dependent variable is Stunting in Toddlers. The instrument in this research is a questionnaire. Results: The results of the research from 33 respondents at the Husada Clinic showed that the majority of toddlers, 59.22%, had the status of pregnant women with CED (Chronic Energy Deficiency). The majority of toddlers, 62.14%, experienced stunting in the short category. Data analysis from the Chi-Square correlation test and asymptotic significance (2-sided) resulted in a p-value of 0.02 < 0.05. The conclusion is that there is a relationship between the nutritional status of pregnant women and stunting in toddlers at the Husada Clinic, Jombang. Conclusion: Based on this research, it can provide input and information to health workers to provide education about nutrition for pregnant women through activities, namely pregnant women's classes and posyandu so that health workers play a big role in efforts to prevent stunting.